THE MILITARY POTENTIAL AND DEVELOPMENT OF MILITARY ART OF THE KHOREZMSHAHS - ANUSHTEGINID STATE - Soyibnazarov U.Sh., (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
This article provides information on the military potential, composition, and size of the Anushteginid dynasty of Khoazmshah , who united twenty-seven states under a single flag in the 13th century, based on an analysis of sources